Aportaciones franciscanas al republicanismo político - Anchústegui Igartua, Esteban; Lázaro Pulido, Manuel (Departamento de Literatura Española-Universidad de Sevilla, 2022)
In this paper we intend to present some medieval foundations, especially Franciscan, of the revitalized civic republicanism of the 20th century. There is an unjustified leap from Rome to the Renaissance that has its origin in the forgetfulness and simplistic view that Hanna Arendt has of medieval thought and Aristotelianism, caused by the historiographic criteria of her time. For this we will show some characteristics of the thought of this new republicanism in order to present the central ideas of four Franciscan authors: Francesc Eiximenis, Bonaventure, Duns Scotus and Alfonso de Castro. First we will try to show the continuity that exists between the Middle Ages and the Modern Age. With this historical approach we intend to analyze that the legitimate aspiration of this new republicanism is distorted and limited if it leaves aside medieval contributions that help to understand more fully the republican pretension the republican pretension that, without rejecting the autonomy of the individual or the sense of community, highlights the interactive nature of social life and instigates him to persevere in the pursuit of the common good.
Franciscan contributions to political republicanism
Keywords: civic republicanism; duns scotus; franciscan thought; Hannah Arendt; medieval philosophy; Scopus; Emerging